The Dynamics of Criticism and Praise among Kyai’s Family Members in Pesantren Environment - Sofyan, Akhmad; Salikin, Hairus; Badrudin, Ali; Muta'allim (International Journal of Educational Research & Social Sciences, 2026)
Language behavior in everyday life often involves activities of criticizing and complimenting. This study aims to describe the forms, types, patterns of delivery, and language usage in the criticism and compliments that are accepted and rejected in the pesantren environment. The data for this study consists of sentences, and the sources of the data are the families of the Kiai in the pesantren community. This research is qualitative, using an anthropolinguistic approach and a communication ethnography method. The data collection method used is the simak libat cakap method. The researcher observed the utterances of criticism and compliments occurring among the members of the Kiai family at Pesantren Tapal Kuda, using recording and note-taking techniques. In addition, interviews were conducted with the Kiai, his family, administrators, teachers, and students to obtain more in-depth data. After the data was collected, the researcher transcribed the utterances into orthographic transcription. The data was then analyzed through reduction, classification, verification, and tabulation processes based on its type. The results of the study indicate that first, there is variation in the use of language adjusted to the context; criticism is often delivered with harsh words if intended to insult, while compliments always use polite language. Second, the forms, types, and patterns of delivering criticism and compliments among the Kiai family members include sarcasm, commands, reprimands, insults, accusations, praise, and motivation. The types of language used include Enjek-Iye (E-I) and Engghi-Enten (E-E), with delivery patterns occurring both directly and indirectly. Third, criticism and compliments that are accepted are generally delivered indirectly and use polite language, while criticism and compliments that are rejected tend to use harsh language, either directly or indirectly. These findings provide new insights into how cultural and religious norms influence the delivery and reception of criticism and compliments in the pesantren environment. The implications of this study emphasize the importance of understanding the social and cultural context in managing interpersonal interactions in the pesantren, as well as providing recommendations for educators and pesantren leaders to be more effective in delivering criticism and compliments in accordance with the prevailing norms.